Studi Etnografi Penyelesaian Sengketa Waris Sunda Wiwitan di Kampung Adat Cirendeu - Nisa Nurfebrianti; Encep Abdul Rojak (UNISBA Press, 2022)
Abstract. This study is based on the customary law applicable to the people who occupy the traditional village of Cirendeu located in Cimahi where the people there have their own rules in solving various problems that occur between the people, including in this case is the inheritance dispute. From the results of the discussion contained in this thesis it can be concluded that the model of inheritance dispute resolution applicable to the community in the traditional village of Cirendeu is deliberation. The deliberations are divided into two stages, namely family deliberations attended by the heirs and related families then if it is not completed in the first stage, traditional deliberations are carried out which are attended by traditional elders. Abstrak. Penelitian ini didasarkan kepada hukum adat yang berlaku pada masyarakat yang menempati Kampung Adat Cirendeu yang terletak di Kota Cimahi di mana masyarakat sana mempunyai aturan tersendiri dalam menyelesaikan berbagai permasalahan yang terjadi diantara masyarakatnya, termasuk dalam hal ini adalah sengketa waris. Dari hasil pembahasan yang tertuang dalam skripsi ini maka dapat disimpulkan bahwa model penyelesaian sengketa waris yang berlaku pada masyarakat di Kampung Adat Cirendeu adalah musyawarah. Musyawarah terbagi ke dalam dua tahap, yaitu musyawarah keluarga yang dihadiri oleh ahli waris dan keluarga yang terkait kemudian apabila tidak selesai pada tahap pertama maka dilakukanlah musyawarah adat yang dihadiri oleh tetua adat.